Fully automated spectrometric protocols for determination of antioxidant activity: advantages and disadvantages - Sochor, Jiri; Ryvolova, Marketa; Krystofova, Olga; Salas, Petr; Hubalek, Jaromir; Adam, Vojtech; Trnkova, Libuse; Havel, Ladislav; Beklova, Miroslava; Zehnalek, Josef; Provaznik, Ivo; Kizek, Rene (Molecules (Basel, Switzerland), 2010)
The aim of this study was to describe behaviour, kinetics, time courses and limitations of the six different fully automated spectrometric methods--DPPH, TEAC, FRAP, DMPD, Free Radicals and Blue CrO5. Absorption curves were measured and absorbance maxima were found. All methods were calibrated using the standard compounds Trolox® and/or gallic acid. Calibration curves were determined (relative standard deviation was within the range from 1.5 to 2.5%). The obtained characteristics were compared and discussed. Moreover, the data obtained were applied to optimize and to automate all mentioned protocols. Automatic analyzer allowed us to analyse simultaneously larger set of samples, to decrease the measurement time, to eliminate the errors and to provide data of higher quality in comparison to manual analysis. The total time of analysis for one sample was decreased to 10 min for all six methods. In contrary, the total time of manual spectrometric determination was approximately 120 min. The obtained data provided good correlations between studied methods (R=0.97-0.99).
Keywords: laboratorní automatizace; časové faktory; Reference Standards; Spectrum Analysis; antioxidancia; Chromans; Gallic Acid; Time Factors; Automation, Laboratory; referenční standardy; Antioxidants; chromany (dihydrobenzopyrany); spektrální analýza; kyselina gallová